Factors Influencing Female Consumer Buying Intention towards Facial Mask in Malaysia - Chin, Jing Huey (2016)
The purpose of the study is to understand the influence of female buying intention towards facial mask in Malaysia. In view of the objectives, there are limitations in literature with regards to the buying intention in facial mask, especially in understanding the reasons influencing the demand of facial mask both locally and overseas. Up to now, the available literature on female buying intention towards facial mask dost not indicate the current phenomenon. Therefore, it is important for this research to be conducted in Malaysia. In order to understand better towards the phenomenon, the independent variables such as acceptability, accessibility, affordability and awareness are to be tested to derive the relationships of the female buying intention towards facial mask. The grounded theory for instance theory of reasoned action will be used as a guide to further understand the buying intention of the respondents. The research methodology is the correlation in nature and the best result is expected to be a positive relationship on the independent variables in the female buying intention of facial mask.